From One to Many Central Plans: Drug Advertising Inspections and Intra-National Protectionism in China - Markus Eberhardt; Zheng Wang; Zhihong Yu (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper provides the first micro-level evidence for the existence and patterns of intra-national protectionism in China. We demonstrate that drug advertising inspections are used by provincial governments to discriminate against firms from outside the province and document how the degree of discrimination varies across firms: manufacturers with closer ties to rival provinces, from provinces with lower presence in the market, and smaller firms are more likely to be targeted. Our findings confirm that giving local governments strong incentives to compete with each other exacerbates the market distortions inherent in a partially reformed economy.
Keywords: F15; P26; L25; 330; intra-national protectionism; drug advertising; China